The literary Qur'an : narrative ethics in the Maghreb - El Shakry, Hoda (Fordham University Press, 2020)
"The novel, the literary adage has it, reflects a world abandoned by God. Yet the possibilities of novelistic form and literary exegesis exceed the secularizing tendencies of contemporary criticism. Showing how the Qurʼan invites critical reading, this account of Arabophone and Francophone Maghrebi literature develops a Qurʼanic model of narratology"--